Effects of 17β-estradiol and 2-methoxyestradiol on the oxidative stress-hypoxia inducible factor-1 pathway in hypoxic pulmonary hypertensive rats - Wang, Li (Exp Ther Med, 2017)
The present study aimed to investigate the effects of 17β-estradiol (E2) and 2-methoxyestradiol (2ME) on the oxidative stress-hypoxia inducible factor-1 (OS-HIF-1) pathway in hypoxic pulmonary hypertensive rats. Female Sprague-Dawley rats were divided randomly into 4 groups, as follows: i) Control (Group A); ii) ovariectomy (OVX) + hypoxia (Group B); iii) OVX + hypoxia + E2 injection (Group C); and iv) 2ME injection (Group D). The rats were maintained under hypoxic conditions for 8 weeks, and mean pulmonary artery pressure (mPAP) and pulmonary arteriole morphology were measured. The reactive oxygen species, superoxide dismutase (SOD), manganese superoxide dismutase (MnSOD), and copper-zinc superoxide dismutase (Cu/ZnSOD) levels in serum were also measured. MnSOD and HIF-1α expression levels in lung tissue were determined by western blotting and reverse transcription-quantitative polymerase chain reaction. The mPAP and arterial remodeling index were significantly elevated following chronic hypoxia exposure; however, experimental data revealed a reduced response in E2 and 2ME intervention rats. Compared with Group A, Group B had significantly elevated oxidative stress levels, as illustrated by increased serum ROS levels, decreased serum SOD and MnSOD levels and decreased MnSOD mRNA and protein expression levels in lung tissue. Furthermore, HIF-1α mRNA and protein expression in Group B was significantly elevated compared with Group A. E2 and 2ME intervention significantly attenuated the aforementioned parameter changes, suggesting that E2 and 2ME partially ameliorate hypoxic pulmonary hypertension. The underlying mechanism of this may be associated with the increase in MnSOD activity and expression and reduction in ROS level, which reduces the levels of transcription and translation of HIF-1α.